Classroom strategies for helping at-risk students - Snow, David; Barley, Zoe A.; Mid-continent Research for Education and Learning (Organization) (Alexandria, VA : Association for Supervision and Curriculum Development, 2005)
This resource for teachers synthesizes the results of 118 studies of students at risk of failure and identifies six general strategies proven to be positive interventions: whole class instruction, cognitively oriented instruction, small groups, tutoring, peer tutoring, and computer-assisted instruction. The authors describe each strategy in turn, analyze the research, and offer implications for deciding how to use the strategy in the classroom. The authors are affiliated with Mid-continent Research for Education and Learning (McREL). Annotation ©2004 Book News, Inc., Portland, OR (booknews.com)
Includes bibliographical references and index.
Keywords: Underachievers -- United States. -- Education (Elementary); Education -- United States. -- tandards; Remedial teaching